Improvement of biomethane production using rumen bacteria in anaerobic cattle manure digesters - Günel, Gülşah. (Thesis (M.S.) - Bogazici University. Institute of Environmental Sciences, 2017., 2017)
One of the most important difficulty of energy production from animal manure in anaerobic conditions is the high cellulose and lignin concentration that limits the speed in hydrolysis stage. Rumen bacteria which reside in the digestive system of herbivores are indicated as an alternative solution to this case. In this study, effect of rumen fluid addition on biogas production and microbial dynamics in batch-wise operated serum bottles with cow manure was investigated. Three experiment sets were conducted, namely Set 1, Set 2 and Set 3 and operated at 36 oC, 41 oC and 43 oC, respectively for 40 days. The highest specific methane yield was found in the Set 2, digester containing 40% as a supportive inocula. Addition of rumen fluid to inoculum effectively improved the bio-methane yield especially in 20 days, resulting in a methane yield of 262 mL CH4/g VS, in which methane content of the biogas was around 52%. Bacterial and methanogenic profiles were detected through NGS-based metagenomics analysis. The phylum Firmicutes, Bacteroidetes and Proteobacteria were determined as the most dominant bacterial phyla. The results from Q-PCR showed that set3, with a high heat of 43 oC, could not set favorable conditions for the rumen bacteria.
Keywords: Anaerobic bacteria.; Rumen -- Microbiology.; Cattle -- Manure.